(untitled) (Research, Society and Development, 2021)
Crassulaceae of the Kalanchoe laetivirens species have ornamental potential, but are poorly studied, especially their reproductive biology and trophic resources made available to visitors. The aim of this study, therefore, was to characterize the reproductive system of K. laetivirens through analyses of floral morphology, trophic resources and floral visitors. Floral structures, pollen / egg ratio, in vitro pollen germination, pollen grain structure in scanning microscopy and the availability of trophic resources by the evaluation of potential and instant nectar were described. The survey of floral visitors was carried out, and the pollen and nectar collection frequencies were recorded. The results show that the species has tubular flowers, complete with tetramer calyx and corolla, eight epipetalous stamens and four pistils with pluriovulated ovaries. Based on pollen / ovule ratio, this species is optionally autogamous. Morphologically, the pollen grain is small, tricolporate and has radial symmetrywith in vitro germination facilitated in the presence of sucrose (20%). Visitors mostly collected pollen with the highest frequency of visits at 9:30 am. The production of instant nectar had little variation between the evaluated times. The results are relevant to the understanding of the reproductive biology of Kalanchoe laetivirens and its relationship with floral visitors.